Software Development for Distinguishing Counterfeit and Genuine Banknotes Using Histogram Color Distribution - Witthaya Boonsuk, (Mathematical Statistician and Engineering Applications, 2023)
The objective of this research was to develop software to distinguish between counterfeit and genuine banknotes using histogram color distribution. The principles of system design and development is based on the cumulative frequency of the color histogram and the intensity of green and blue. To be used to classify banknotes by analyzing the color from the cumulative frequency of colors in histogram The results of system proficiency from the testing collected from 5 group samples, 10 images per each group, 50 images in total showed that the precision of group 1: 1,000 Baht banknote was 90%; group 2: 500 Baht banknote was 90%; group 3: 100 Baht banknote was 90%; group 4: 50 Baht banknote was 90%; and group 5: 50 Baht banknote was 90%. Overview of the system considered excellent demonstrated Analyzing the cumulative frequency of the color histogram in conjunction with the chromaticity of the pixels. quite accurate Therefore, it is suitable to be applied in classifying domestic and foreign currency banknotes with this principles in the future.